Exploratory Study on the Impact of COVID-19 Pandemic on the Online Mentoring Processes - Rindu Salsabila; Surya Asih Pratiwi; Muhamad Dandi Anada Putra (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This research is motivated by a pandemic that is experienced throughout the world, especially Indonesia. The presence of the COVID-19 virus pandemic has an impact on various fields, one of which is education. The purpose of this study was to identify and obtain information about the obstacles to the online mentoring process due to the COVID-19 virus pandemic. This research uses an exploratory case study method and the research approach uses a qualitative case study method which is used to obtain information on the constraints and consequences of the COVID-19 virus pandemic on the mentoring process activities at the Faculty of Economics and Business, Muhammadiyah University of Surakarta. For confidentiality purposes, respondents were given the initials R1, R2, R3, R4, R5, and R6. Semi-structured interviews were conducted online and a list of questions compiled for interviews was developed based on related literature. Respondents for this study were BPH KMF and Pementors at the Faculty of Economics and Business Muhammadiyah Surakarta. The results of this study are that there are obstacles in the teaching and learning process in online mentoring in the form of signal constraints and limited internet quota, so that material and information lags often occur which lead to miscommunication.